CAUSES AND TYPES OF ANARTHRIA SPEECH DEFICIENCY - Iminjonova Mokhichehra Alimardon qizi (THE PLACE AND ROLE OF TURKEY AND THE NEAR REGION IN THE PROCESSES OF SCIENTIFIC, SOCIAL, AND CULTURAL DEVELOPMENT, 2026)
This article provides a scientific overview of the factors contributing to anarthria speech disorder, its formation mechanism, clinical manifestations, and classification from the perspective of speech therapy and neuropsychology. The neurological basis of this condition, the pathogenesis associated with damage to brain structures, and classifications proposed by foreign researchers are analyzed.